Cohesion of Discourse in Background Research Paper - Hilyati Fitria Harahap; Rizki Azima; Emeliya Sukma Dara Damanik; Ainan Ningrum (Jurnal Dunia Pendidikan, 2024)
This research is to find out how cohesion is used in the background research paper. Because cohesion is an important criterion and principle in a text. It is hoped that this research can contribute to the development of the quality of background research writing. So that the background research can be understood and is useful for readers. The method used to analyze cohesion is descriptive analysis which is visible in each paragraph. The cohesion aspects analyzed are lexical and grammatical cohesion aspects. The results of this research show that the background research paper has aspects of lexical cohesion and grammatical cohesion. Cohesion aspect where discourse can convey messages to readers. That way, the content of the background research can make readers better understand the author's intentions